SO2 removal with ferric sulfate solution - Jiang, J-H (Environmental technology, 2008)
The determination of the influence of the concentration of ferric sulfate solution on SO2 absorption was performed in this study. It was found that the SO2 absorption efficiency increased with increasing ferric concentration, and decreased with the acidity of the spraying solution. As the hydrolysis of ferric ions occurs in solution, the SO2 removal efficiency increased slowly with increasing Fe(III) concentration. Taking into account the hydrodynamic and mass transfer characteristics of the packed column, the enhancement factor (E) was found to depend on the concentration of the ferric ions and pH, which indicated that it could be used for the simulation or design of SO2 scrubbers